PENGARUH KEPEMIMPINAN, SELF EFFICACY, DAN KOORDINASI TERHADAP KINERJA APARATUR SIPIL NEGARA (ASN) SEKRETARIAT DAERAH KABUPATEN LIMA PULUH KOTA - Ikhsani Novella; Putri Armawinda; Afdila Afdila; Ahmad Rizqa Fauzi; Syamsir Syamsir (Ensiklopedia of Journal, 2022)
As a State Civil Apparatus (ASN) who handles the administration of other ASN personnel in the Regency of Lima Puluh Kota, the ASN of the Regional Secretariat of Lima Puluh Kota Regency is expected to carry out their roles and functions professionally. It was known that leadership, self-efficacy, and coordination can affect the level of professionalism of employees, which will be reflected in their performance achievements. This study aimed to determine the effect of leadership, self-efficacy, and coordination on the performance of ASN at the Regional Secretariat of Lima Puluh Kota Regency. This research was a descriptive-qualitative-research that conducted from October to November 2021 at the Regional Secretariat of Lima Puluh Kota Regency. The results of this study indicated that leadership, self-efficacy, and coordination affect the performance of the ASN at the Regional Secretariat of Lima Puluh Kota Regency significantly, either partially or simultaneously. This research is expected to provide scientific data in improving the performance of ASN at the Regional Secretariat of Lima Puluh Kota Regency.